BIOM-38. THE PROGNOSTIC ROLE OF THE IMMUNOHISTOCHEMICAL MARKERS H3K27me3, SSTR1-5 AND BAP1 IN MENINGIOMA. (12th November 2021) - Behling, Felix; Fodi, Christina; Renovanz, Mirjam; Paulsen, Frank; Skardelly, Marco; Honegger, Jürgen; Tatagiba, Marcos; Schittenhelm, Jens; Tabatabai, Ghazaleh
Abstract: Meningiomas are the most common primary tumors of the nervous system. These slow growing tumors arise from the meninges. Most patients can be cured by surgical excision. Yet, approximately 20% of patients suffer tumor recurrence. Prognostic markers are warranted to facilitate the identification of patients with an increased risk of tumor recurrence. Immunohistochemical markers are very interesting candidates in this regard and could be integrated into the routine clinical workflow as an inexpensive tool for prognostication and risk stratification. We analyzed the prognostic impact of the immunohistochemical expression of H3K27me3, somatostatin receptors 1-5 and BAP1 in the Tübingen meningioma cohort including > 1200 meningiomas. We identified an independent negative prognostic impact of the loss of H3K27me3. An increased expression score for SSTR2A was associated with a shorter progression-free survival. Higher expression of SSTR5 indicated a more favorable prognosis. The loss of BAP1 expression in meningioma cells was a negative prognostic factor with a shorter progression-free survival. Taken together, we present potential candidate prognostic markers that could be further investigated in prospective cohorts to determine their clinical utility.